Dualisme Gelombang-Partikel: Landasan Teori, Transformasi Konsep Ilmiah, dan Implikasi pada Fisika Modern - Margareth Jacoba Da Gomes; Elisabeth Endang Permata Simbolon; Loni Ignasia Lingga; Miftahul Jannah; Rizki Salsabila Batubara; Deo Demonta Panggabean; Ladestam Sitinjak (Kappa Journal, 2025)
Wave–particle dualism is a fundamental concept that has shaped physics since the early twentieth century and remains central to modern physics research. This study aims to examine the development of wave–particle dualism through three key phenomena: black-body radiation, the photoelectric effect, and Compton scattering. The method employed is a systematic literature review of 10 peer-reviewed journal articles published between 2018 and 2024, focusing on theoretical perspectives, experimental evidence, and conceptual implications. The results indicate that research on black-body radiation has progressed from the development of high-precision radiation sources toward the control of atomic energy shifts and light polarization. Studies on the photoelectric effect reveal its dual role as both an effective educational tool through simple, low-cost experiments and a platform for advanced investigations of electron momentum distribution. Meanwhile, research on Compton scattering spans practical applications such as radiation detector calibration and theoretical modeling of photon–electron interactions in extreme quantum fields. Overall, this study demonstrates that wave–particle dualism is not merely a historical concept but an evolving framework that continues to inform theoretical development, experimental validation, and technological innovation. The findings have implications for physics education, experimental design, and future research on quantum phenomena by highlighting the interconnected nature of foundational quantum effects.